Impact of gas pressure on particle feature in Fe-based amorphous alloy powders via gas atomization: Simulation and experiment. (10th April 2022) - Shi, Yutong; Lu, Weiyan; Sun, Wenhai; Zhang, Suode; Yang, Baijun; Wang, Jianqiang
Highlights: The flow dynamics of the gas phase and gas-melt two-phase fields, and the break-up process were illustrated. The particle size distributions of simulated results were consistent with the powder experimental tests. The Fe-based alloy powders with diameters in the range of 25–45 μm were found to be a fully amorphous phase. Abstract: Gas atomization is now an important production technique for Fe-based amorphous alloy powders used in additive manufacturing, particularly selective laser melting, fabricating large-sized Fe-based bulk metallic glasses. Using the realizable k-ε model and discrete phase model theory, the flow dynamics of the gas phase and gas-melt two-phase flow fields in the close-wake condition were investigated to establish the correlation between high gas pressure and powder particle characteristics. The locations of the recirculation zones and the shapes of Mach disks were analyzed in detail for the type of discrete-jet closed-coupled gas atomization nozzle. In the gas-phase flow field, the vortexes, closed to the Mach disk, are found to be a new deceleration method. In the two-phase flow field, the shape of Mach disk changes from " S "-shape to " Z "-shape under the impact of the droplet flow. As predicted by the wave model, with the elevation of gas pressure, the size of the particle is found to gradually decrease and its distribution becomes more concentrated. Simulation results were compliant with the Fe-based amorphous alloy powder preparation tests. This study deepens the understanding of the gas pressure impacting particle features via gas atomization, and contributes to technological applications. Graphical abstract: Image, graphical abstract